2003
DOI: 10.1515/astro-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Applications of the Synchronous Network of Remote Telescopes

Abstract: A new approach for the search of microvariability and high-speed phenomena in variable stars is presented. It gives a new technology of observation and analysis of the data. Statistical photometry stands on the three pillars: the digital filtering technique, the photon counting statistics based on the Mandel equation, and the integral transforms of the light curves. This technique permits to investigate low-amplitude and rapid variability of stars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…We also note that, after a rapid decline in error as the S/N increases, the asymptotic behavior of σm for very large S/N may explain, in part, why it is so difficult to achieve photometric precisions smaller than a few milli-mag. While at S/N ∼ 100 we predict σm ∼ 11 [mmag], at S/N ∼ 200 we would have σm ∼ 5 [mmag], consistent with actual measurements, as quoted by Zhilyaev et al (2005) (see also Warner (2006, Section 4 and Table 4.1)).…”
Section: Analysis and Interpretation Of The 2d Cramér-rao Boundsupporting
confidence: 89%
“…We also note that, after a rapid decline in error as the S/N increases, the asymptotic behavior of σm for very large S/N may explain, in part, why it is so difficult to achieve photometric precisions smaller than a few milli-mag. While at S/N ∼ 100 we predict σm ∼ 11 [mmag], at S/N ∼ 200 we would have σm ∼ 5 [mmag], consistent with actual measurements, as quoted by Zhilyaev et al (2005) (see also Warner (2006, Section 4 and Table 4.1)).…”
Section: Analysis and Interpretation Of The 2d Cramér-rao Boundsupporting
confidence: 89%
“…Possibly, the 160 s periodic oscillations observed by Houdebine et al (1993) observed by Zhilyaev et al (2000) in EV Lac flares have the same nature.…”
Section: Introductionmentioning
confidence: 78%
“…The cited Crimean results have been obtained from the flare monitoring with a rather low time resolution of about 20 s. The technique of digital filtering recently employed by Zhilyaev et al (2000) allows the time resolution to improve by 2 orders of magnitude. The first application of the technique resulted in the discovery of HFO in brightness and colors of the detected flares (Zhilyaev et al 2000(Zhilyaev et al , 2003.…”
Section: Introductionmentioning
confidence: 99%